Faktor-Faktor yang Mempengaruhi Likuiditas pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) - Nawang Kalbuana; Ruth Marito Maritho Lumban Gaol; Benny Kurnianto (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2021)
This study aims to test the factors that affect liquidity. This study uses companies listed in the Jakarta Islamic Index with a period of 2016 to 2020. There are 17 companies that are used as research objects. The study used multiple linear regression analysis with the help of SPSS application applications. The study finds that audit quality and leverage had an effect on liquidity. While other variables such as dividend policy, free cash flow and profitability have no effect on liquidity.